Learning Through Projects: A Path to Better Student Collaboration - Alonemarera, A. S.; Mardin, Herinda (Journal of Biological Science and Education, 2025)
Collaboration skills are one of the 21st-century skills that are very important for students, especially in facing the challenges of the complex world of work and social life. Students' collaboration skills in the Biology Education Study Program at Universitas Sembilanbelas November (USN), Kolaka, are still relatively low. One approach believed to improve students' collaboration skills is the application of Project-Based Learning (PjBL). Thus, this study aims to determine the effect of the application of Project-Based Learning on the collaboration skills of students in the Biology Education Study Program at USN Kolaka. This study is a pre-experimental type using a one-group pretest-posttest design. The subjects of the study were all active students (16 people) of the biology education study program, even the semester of the 2024/2025 academic year, who took the course "Media dan Sumber Pembelajaran Biologi". Data on students' collaboration skills were obtained using a collaboration skill observation sheet. Data analysis used an inferential test of the paired sample t-test type. The results of the study showed that the average collaboration skill of students before treatment was 30.77, and during treatment was 83.64. From the results of the inferential test, the Sig. The value was obtained. 0.000 0.05. This study concludes that there is a positive effect of the implementation of PjBL on students' collaboration skills. These findings indicate that PjBL can create a learning environment that encourages active participation, shared responsibility, effective communication, and constructive teamwork. Therefore, PjBL can be a strategic alternative for improving students' collaborative soft skills sustainably in higher education environments. Keywords:  collaboration, project-based learning